Antioxidant properties of turmeric rhizome and leaf (Curcuma Longa. L) and its effects on the oxidative stability of beef patty / Fatimah Zahrah Darmadi, Marina Zulkifli and Nina Naquiah Ahmad Nizar - Darmadi, Fatimah Zahrah; Zulkifli, Marina; Ahmad Nizar, Nina Naquiah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Beef patties are made from meat. Meat contains the most protein among all foods and contains essential amino acids required in human diet. Nonetheless, beef patties are susceptible to oxidative deterioration, which is the source of limitation in the quality of the beef patty. This is due to lipid oxidation that produces products such as ketones, alcohols, aldehydes, and other toxic compounds. These substances have an adverse effect on colour, texture, and flavour. Thus, this study will focus on the antioxidant incorporation of the turmeric rhizome and leaf into the beef patty. The antioxidant activity of turmeric rhizome extract (TRE) and turmeric leaf extract (TLE) was analysed using three different methods which are Free Radical Scavenging (DPPH), Ferric Reducing Antioxidant Power (FRAP) and Total Phenolic Compound (TPC). Peroxide Value (PV) was performed on the beef patty incorporated with turmeric rhizome extract. This study assessed the antioxidant characteristics of turmeric rhizome extract and turmeric leaves extract, and whether turmeric rhizome extract exhibited antioxidant properties when added to beef patties.